The complete chloroplast genome of Fissidens nobilis Griff. (Fissidentaceae, Bryophyta) - Woochan Kwon; Juhyeon Min; Hong Xi; Jongsun Park (Mitochondrial DNA. Part B. Resources, 2019)
We presented a complete chloroplast genome of Fissidens nobilis which is 124,962 bp long and has four subregions: 86,122 bp of large single-copy (LSC) and 18,708 bp of small single-copy (SSC) regions are separated by 10,066 bp of inverted repeat (IR) regions including 127 genes (82 protein-coding genes, 8 rRNAs, and 37 tRNAs). The overall GC content is 29.2% and those in the LSC, SSC, and IR regions are 26.6%, 26.0%, and 43.5%, respectively. Phylogenetic trees show that the phylogenetic position of F. nobilis is congruent with the previous phylogenetic study of moss species.